High Performance Computing on the Cloud via HPC+Cloud software framework - Balakrishnan, S.; Veeramani, S.; Leong, J.; Murray, I.; Sidhu, Amandeep (2017)
© 2016 IEEE.There is an increased need for scalable high performance computing systems as the amount of generated data grows. Traditional High Performance Computing (HPC) clusters built to handle big data processing have inherent weaknesses that can be overcome by migrating to a more flexible cloud computing environment. This article discusses high performance computing and the paradigm shift from traditional onsite computing clusters to using the cloud for the same tasks. This article also proposes a solution called HPC+Cloud that enables enterprises to migrate to, and subsequently manage, high performance computing on the cloud. HPC+Cloud manages multiple, disparate, nodes on the hybrid cloud over software defined networks to complete tasks in a queue.